Revisiting the follicle-stimulation hormone receptor expression and function in human myometrium and adipose tissue - Palak, Ewelina; Ponikwicka-Tyszko, Donata; Pulawska-Moon, Kamila; Sztachelska, Maria; Milewska, Gabriela; Modzelewska, Beata; Kleszczewski, Tomasz; Koivukoski, Maria L.; Bernaczyk, Piotr; Hady, Hady Razak; Gołaszewski, Piotr; Lupinska, Aleksandra N.; et al. (Springer Science and Business Media LLC, 2025)
Background
Extragonadal follicle-stimulating hormone receptor (FSHR) expression at low levels has been shown in several normal and tumor tissues, including myometrium and adipose tissue. FSH-FSHR signaling in the myometrium has been suggested to regulate uterine contractile activity and the timing of labor. In contrast, FSH-FSHR has been linked to the activation of brown/beige fat thermogenesis in adipose tissue. The issue of extragonadal FSHR expression and its functionality remains contentious within the scientific community, as contradictory findings necessitate further independent and critical analyses. Hereby, we re-investigated the FSHR expression and its functionality in normal non-pregnant (M-NP) and pregnant (N-P) human myometrium, as well as in human visceral (VAT) and subcutaneous (SCAT) adipose tissue (AT).
Methods
FSHR expression at mRNA (real-time qPCR, RNAscope in situ hybridization) and protein (immunohistochemical staining) levels in adipose tissue, myometrium, and adipocytes were evaluated. Myometrium and adipocytes were treated with recombinant (rh)FSH to study its effects on functional pathways. Myometrium contractile activity was measured using a force transducer with digital output and the DASYLab software unit. Cyclic adenosine monophosphate (cAMP) production by myometrium explants and adipocytes was measured using a cAMP ELISA Kit. The activation of the AKT pathway in myometrium and adipocytes was analyzed by Western blot analysis.
Results
Contrary to previous observations, we found no expression of FSHR at either mRNA or protein levels in M-NP, N-P, VAT, and SCAT. Treatment with recombinant human FSH (rhFSH) showed no effect on cAMP production or phosphorylation of AKT in M-NP, N-P, as well as in VAT and SCAT. rhFSH treatment did not influence contractile activity in M-NP, N-P.
Conclusions
These findings suggest that the FSHR signaling pathway does not regulate myometrial contractility during pregnancy. Additionally, the absence of FSHR expression in both VAT and SCAT implied that FSHR does not play a role in the functional signaling pathways in adipose tissues. In conclusion, our findings contradict earlier data on the involvement of FSH-FSHR signaling in regulating myometrial contractility near term, as well as in adipose tissue function.